THE CORRELATION BETWEEN THE FIRST SEMESTER STUDENTS’ LEARNING STYLES TOWARD THEIR ENGLISH ACHIEVEMENT AT STAI BUMI SILAMAPARI LUBUKLINGGAU - Joni Helandri (El-Ghiroh : Jurnal Studi Keislaman, 2017)
The problem encountered by students on their English achievement was correlated with their learning styles. Therefore, this research aimed to find out whether or not there is a correlation between the first semester students’ learning styles and their English achievement at STAI Bumi Silampari Lubuklinggau in the academic year of 2016/2017. Out of this population 20 students were recruited as the sample. The data were collected through questionnaires and English Semester test. Based on the result of questionnaire, it can revealed that there were 4 students or 20% who learned their English styles through Audio Visual Styles, there were 11 students or 55% who learned their English styles through Visual Styles and there were 6 students or 30% who learned their English styles through Kinestetic Styles. In addition, the findings also revealed that that the correlation coefficient or the result of the robt was 0.46 and the critical value of the rtable was 0.388 at the level significance 0.005 or 5%. Since robt was higher than rtable the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected (robt > rtable). It means that there was correlation between first semester students’ learning styles and students’ English achievement at STAI Bumi Silampari Lubuklinggau in the academic year 2016/2017